Lightweight high-strength composite material

By using the combination and specific processes of carbon fiber, glass fiber, nano-silica and other materials in composite materials, the problems of high benzene and formaldehyde content and insufficient performance in existing composite sheets are solved, and lightweight, high strength and high Durable composite materials to meet high performance needs in specific fields.

CN119220053APending Publication Date: 2024-12-31CHONGQING AEROSPACE POLYTECHNIC COLLEGE
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411356273.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing composite sheets are unable to meet the high content of benzene and formaldehyde in the glue, which affects the use range, and their strength and poor durability.

Method used

Lightweight high-strength composite materials are prepared by surface treatment and hot press forming process using a combination of carbon fiber, glass fiber, nano-silica, polyamide, epoxy resin, curing agent, coupling agent, toughening agent and dispersing agent. , improve the density, durability and toughness of the material.

Benefits of technology

It significantly improves the tensile strength, elastic modulus and durability of the composite material, reduces the brittleness of the material, enhances the thermal stability and service life of the material, and reduces weight.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220053A_ABST
    Figure CN119220053A_ABST
Patent Text Reader

Abstract

The invention provides a lightweight high-strength composite material, and relates to the technical field of composite materials. The light-weight high-strength composite material comprises the following raw materials in parts by weight: 30-50 parts of carbon fibers, 20-40 parts of glass fibers, 5-10 parts of nano silicon dioxide, 20-30 parts of polyamide, 40-60 parts of epoxy resin, 5-10 parts of a curing agent, 2-5 parts of a coupling agent, 3-8 parts of a toughening agent and 1-3 parts of a dispersing agent. The high-strength carbon fibers and glass fibers are adopted, so that the composite material has higher tensile strength and elasticity modulus, the high-strength characteristic of the material is ensured, the structure of the composite material is more compact by introducing nano silicon dioxide, and the durability and stability of the material are improved; secondly, the epoxy resin has good corrosion resistance and can protect the reinforcing material from being corroded, the service life of the composite material is prolonged, the curing agent, the coupling agent, the flexibilizer and the dispersing agent are used, the preparation process of the composite material is more efficient, and meanwhile the comprehensive performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, in particular to lightweight and high-strength composite materials. Background Art

[0002] With the development of science and technology and the improvement of people's living standards, more and more materials are used in daily life, but a single board can no longer meet people's needs. At the same time, today's composite boards are generally PP wood powder composite boards, wood fiber plywood boards, PP glass fiber honeycomb boards, etc.

[0003] However, all of the above-mentioned boards are synthesized through a complex process using glue. Because the content of benzene and formaldehyde in the glue is relatively high, it affects the use of the boards. Among various boards currently used, the most widely used is PP glass fiber honeycomb board, which uses a small amount of glue and also contains a small amount of harmful substances such as benzene and formaldehyde, which is not conducive to use.

[0004] Secondly, some composite materials have problems such as insufficient strength and poor durability, which cannot meet the high requirements for material performance in specific fields. Therefore, it is particularly important to develop a composite material that is both lightweight and high-strength. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the deficiencies of the prior art, the present invention provides a lightweight and high-strength composite material to solve the problems raised by the above-mentioned background technology.

[0007] (II) Technical solution

[0008] To achieve the above objectives, the present invention is implemented through the following technical scheme: a lightweight high-strength composite material, comprising the following raw materials in parts by weight: 30-50 parts of carbon fiber, 20-40 parts of glass fiber, 5-10 parts of nano-silicon dioxide, 20-30 parts of polyamide, 40-60 parts of epoxy resin, 5-10 parts of curing agent, 2-5 parts of coupling agent, 3-8 parts of toughening agent, and 1-3 parts of dispersant.

[0009] Carbon fiber has the characteristics of high strength, high modulus and low density, which can significantly improve the strength and stiffness of composite materials while reducing the weight of the material. Glass fiber has good heat resistance, corrosion resistance and insulation, and works synergistically with carbon fiber to further enhance the performance of composite materials. Nano-silica can fill the pores in the material and improve the density and strength of the material. Polyamide has excellent mechanical properties and chemical resistance and can provide good matrix support. Epoxy resin, as a matrix material, has good adhesion and chemical corrosion resistance. Curing agent is used to cure epoxy resin to form a strong three-dimensional network structure. Coupling agent can improve the interfacial bonding between fiber and resin and improve the performance of composite materials. Toughening agent can improve the toughness of composite materials and reduce the possibility of brittle fracture. Dispersant helps to evenly disperse nano-silica to avoid agglomeration, thereby ensuring the uniformity of material properties.

[0010] Preferably, the following raw materials are included in parts by weight: 40 parts of carbon fiber, 30 parts of glass fiber, 8 parts of nano-silicon dioxide, 25 parts of polyamide, 50 parts of epoxy resin, 8 parts of curing agent, 4 parts of coupling agent, 6 parts of toughening agent, and 2 parts of dispersant.

[0011] Preferably, the carbon fiber is a high-strength carbon fiber with a tensile strength of not less than 5000 MPa and an elastic modulus of not less than 300 GPa.

[0012] Preferably, the glass fiber is an alkali-free glass fiber, and its tensile strength is not less than 2000 MPa and its elastic modulus is not less than 70 GPa.

[0013] Preferably, the curing agent is any one of an amine curing agent, an acid anhydride curing agent, and an imidazole curing agent; specifically, the amine curing agent is ethylenediamine, the acid anhydride curing agent is phthalic anhydride, and the imidazole curing agent is 2-methylimidazole.

[0014] Preferably, the coupling agent is any one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent; specifically, the silane coupling agent is KH-550, the titanate coupling agent is NDZ-101, and the aluminate coupling agent is DL-411.

[0015] Preferably, the toughening agent is any one of a thermoplastic elastomer, rubber particles, and a thermosetting resin; specifically, the thermoplastic elastomer is a polyurethane elastomer, the rubber particles are nitrile rubber particles, and the thermosetting resin is an epoxy resin toughening agent.

[0016] Preferably, the dispersant is any one of a surfactant, a polymer dispersant, and an inorganic dispersant; specifically, the surfactant is sodium dodecyl sulfate, the polymer dispersant is polyvinyl alcohol, and the inorganic dispersant is silica microspheres.

[0017] Preferably, the method for preparing the composite material comprises the following steps:

[0018] Step 1: Surface treatment of carbon fiber and glass fiber to remove impurities and oil stains on the fiber surface;

[0019] Step 2: Add nano-silicon dioxide to polyamide and epoxy resin, stir evenly to obtain a mixed resin;

[0020] Step 3: Add the surface treated carbon fiber and glass fiber into the mixed resin and stir evenly to obtain a prepreg;

[0021] Step 4: Add curing agent, coupling agent, toughening agent and dispersant to the prepreg, stir evenly, and obtain a composite material raw material;

[0022] Step 5: Place the composite material raw material into a mold and perform hot pressing to obtain a lightweight and high-strength composite material.

[0023] Preferably, in step five, the hot pressing molding is performed at a pressure of 10-20 MPa, a temperature of 120-150° C., and a time of 1-2 hours.

[0024] (III) Beneficial effects

[0025] The present invention provides a lightweight and high-strength composite material, which has the following beneficial effects:

[0026] 1. The use of high-strength carbon fiber and alkali-free glass fiber makes the composite material of the present invention have higher tensile strength and elastic modulus, thereby ensuring the high-strength characteristics of the material. By introducing nano-silicon dioxide, the structure of the composite material is more compact, the durability and stability of the material are improved, and the addition of nano-silicon dioxide also enhances the thermal stability of the material.

[0027] 2. Epoxy resin has good corrosion resistance, can protect the reinforcing material from corrosion, and improve the service life of the composite material. The use of preferred curing agent, coupling agent, toughening agent and dispersant makes the preparation process of the composite material more efficient, while improving the comprehensive performance of the material, increasing the toughness of the material and reducing the brittleness of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic flow chart of the preparation method of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Embodiment 1:

[0031] An embodiment of the present invention provides a lightweight and high-strength composite material, including the following raw materials in parts by weight: 30 parts of carbon fiber, 20 parts of glass fiber, 5 parts of nano-silicon dioxide, 20 parts of polyamide, 40 parts of epoxy resin, 5 parts of curing agent, 2 parts of coupling agent, 3 parts of toughening agent, and 1 part of dispersant.

[0032] Carbon fiber has the characteristics of high strength, high modulus and low density, which can significantly improve the strength and stiffness of composite materials while reducing the weight of the material. Glass fiber has good heat resistance, corrosion resistance and insulation, and works synergistically with carbon fiber to further enhance the performance of composite materials. Nano-silica can fill the pores in the material and improve the density and strength of the material. Polyamide has excellent mechanical properties and chemical resistance and can provide good matrix support. Epoxy resin, as a matrix material, has good adhesion and chemical corrosion resistance. Curing agent is used to cure epoxy resin to form a strong three-dimensional network structure. Coupling agent can improve the interfacial bonding between fiber and resin and improve the performance of composite materials. Toughening agent can improve the toughness of composite materials and reduce the possibility of brittle fracture. Dispersant helps to evenly disperse nano-silica to avoid agglomeration, thereby ensuring the uniformity of material properties.

[0033] The carbon fiber is a high-strength carbon fiber with a tensile strength of not less than 5000 MPa and an elastic modulus of not less than 300 GPa. The glass fiber is an alkali-free glass fiber with a tensile strength of not less than 2000 MPa and an elastic modulus of not less than 70 GPa.

[0034] Secondly, the curing agent is an amine curing agent, and specifically, the amine curing agent is ethylenediamine.

[0035] Secondly, the coupling agent is a silane coupling agent, and specifically, the silane coupling agent is KH-550.

[0036] Secondly, the toughening agent is a thermoplastic elastomer, and specifically, the thermoplastic elastomer is a polyurethane elastomer.

[0037] Secondly, the dispersant is a surfactant, and specifically, the surfactant is sodium dodecyl sulfate.

[0038] like Figure 1As shown, the embodiment of the present invention also provides a method for preparing the composite material, comprising the following steps:

[0039] Step 1: Preprocessing:

[0040] Surface treatment of carbon fiber and glass fiber to remove impurities and oil stains on the fiber surface;

[0041] Step 2: Prepare mixed resin:

[0042] Adding nano-silicon dioxide into polyamide and epoxy resin, stirring evenly to obtain a mixed resin;

[0043] Step 3: Preparing prepreg:

[0044] Adding the surface-treated carbon fiber and glass fiber into the mixed resin and stirring evenly to obtain a prepreg;

[0045] Step 4: Preparation of composite materials:

[0046] Adding a curing agent, a coupling agent, a toughening agent and a dispersant into the prepreg, stirring evenly, to obtain a composite material raw material;

[0047] Step 5: Hot Pressing:

[0048] The composite material raw material is placed in a mold and hot-pressed. The hot-pressing pressure is 10 MPa, the temperature is 120° C., and the time is 1 hour, thereby obtaining a lightweight and high-strength composite material.

[0049] Embodiment 2:

[0050] An embodiment of the present invention provides a lightweight and high-strength composite material, including the following raw materials in parts by weight: 40 parts of carbon fiber, 30 parts of glass fiber, 8 parts of nano-silicon dioxide, 25 parts of polyamide, 50 parts of epoxy resin, 8 parts of curing agent, 4 parts of coupling agent, 6 parts of toughening agent, and 2 parts of dispersant.

[0051] The carbon fiber is a high-strength carbon fiber with a tensile strength of not less than 5000 MPa and an elastic modulus of not less than 300 GPa. The glass fiber is an alkali-free glass fiber with a tensile strength of not less than 2000 MPa and an elastic modulus of not less than 70 GPa.

[0052] Secondly, the curing agent is an acid anhydride curing agent, and specifically, the acid anhydride curing agent is phthalic anhydride.

[0053] Secondly, the coupling agent is a titanate coupling agent, and specifically, the titanate coupling agent is NDZ-101.

[0054] Secondly, the toughening agent is rubber particles, and specifically, the rubber particles are nitrile rubber particles.

[0055] Secondly, the dispersant is a polymer dispersant, and specifically, the polymer dispersant is polyvinyl alcohol.

[0056] like Figure 1 As shown, the embodiment of the present invention also provides a method for preparing the composite material, comprising the following steps:

[0057] Step 1: Preprocessing:

[0058] Surface treatment of carbon fiber and glass fiber to remove impurities and oil stains on the fiber surface;

[0059] Step 2: Prepare mixed resin:

[0060] Adding nano-silicon dioxide into polyamide and epoxy resin, stirring evenly to obtain a mixed resin;

[0061] Step 3: Preparing prepreg:

[0062] Adding the surface-treated carbon fiber and glass fiber into the mixed resin and stirring evenly to obtain a prepreg;

[0063] Step 4: Preparation of composite materials:

[0064] Adding a curing agent, a coupling agent, a toughening agent and a dispersant into the prepreg, stirring evenly, to obtain a composite material raw material;

[0065] Step 5: Hot Pressing:

[0066] The composite material raw material is placed in a mold and hot-pressed. The hot-pressing pressure is 15 MPa, the temperature is 135° C., and the time is 1.5 hours to obtain a lightweight and high-strength composite material.

[0067] Embodiment three:

[0068] An embodiment of the present invention provides a lightweight and high-strength composite material, including the following raw materials in parts by weight: 50 parts of carbon fiber, 40 parts of glass fiber, 10 parts of nano-silicon dioxide, 30 parts of polyamide, 60 parts of epoxy resin, 10 parts of curing agent, 5 parts of coupling agent, 8 parts of toughening agent, and 3 parts of dispersant.

[0069] The carbon fiber is a high-strength carbon fiber with a tensile strength of not less than 5000 MPa and an elastic modulus of not less than 300 GPa. The glass fiber is an alkali-free glass fiber with a tensile strength of not less than 2000 MPa and an elastic modulus of not less than 70 GPa.

[0070] Secondly, the curing agent is an imidazole curing agent, and specifically, the imidazole curing agent is 2-methylimidazole.

[0071] Secondly, the coupling agent is an aluminate coupling agent, and specifically, the aluminate coupling agent is DL-411.

[0072] Secondly, the toughening agent is a thermosetting resin, and specifically, the thermosetting resin is an epoxy resin toughening agent.

[0073] Secondly, the dispersant is an inorganic dispersant, and specifically, the inorganic dispersant is silica microspheres.

[0074] like Figure 1 As shown, the embodiment of the present invention also provides a method for preparing the composite material, comprising the following steps:

[0075] Step 1: Preprocessing:

[0076] Surface treatment of carbon fiber and glass fiber to remove impurities and oil stains on the fiber surface;

[0077] Step 2: Prepare mixed resin:

[0078] Adding nano-silicon dioxide into polyamide and epoxy resin, stirring evenly to obtain a mixed resin;

[0079] Step 3: Preparation of prepreg:

[0080] Adding the surface-treated carbon fiber and glass fiber into the mixed resin and stirring evenly to obtain a prepreg;

[0081] Step 4: Preparation of composite materials:

[0082] Adding a curing agent, a coupling agent, a toughening agent and a dispersant into the prepreg, stirring evenly, to obtain a composite material raw material;

[0083] Step 5: Hot Pressing:

[0084] The composite material raw material is placed in a mold and hot-pressed. The hot-pressing pressure is 20 MPa, the temperature is 150° C., and the time is 2 hours, so that a lightweight and high-strength composite material is obtained.

[0085] Comparative Example 1:

[0086] The difference between the comparative example 1 and the embodiment 1 is that the lightweight high-strength composite material includes the following raw materials in parts by weight: 30 parts of carbon fiber, 20 parts of glass fiber, 20 parts of polyamide, 40 parts of epoxy resin, 5 parts of curing agent, 2 parts of coupling agent, 3 parts of toughening agent, and 1 part of dispersant.

[0087] Comparative Example 2:

[0088] The difference between the second comparative example and the first exemplary embodiment is that the lightweight high-strength composite material comprises the following raw materials in parts by weight: 20 parts of glass fiber, 5 parts of nano-silicon dioxide, 20 parts of polyamide, 40 parts of epoxy resin, 5 parts of curing agent, 2 parts of coupling agent, 3 parts of toughening agent, and 1 part of dispersant.

[0089] Comparative Example 3:

[0090] The difference between the comparative example 3 and the embodiment 1 is that the lightweight high-strength composite material includes the following raw materials in parts by weight: 30 parts of carbon fiber, 5 parts of nano-silicon dioxide, 20 parts of polyamide, 40 parts of epoxy resin, 5 parts of curing agent, 2 parts of coupling agent, 3 parts of toughening agent, and 1 part of dispersant.

[0091] Experimental example:

[0092] The performance tests were conducted on the composite materials prepared in Examples 1, 2, 3 and Comparative Examples 1, 2, 3. The test results are shown in the following table:

[0093] Example Tensile strength(MPa) Bending strength(MPa) <![CDATA[Impact strength (kJ / m 2 )]]> <![CDATA[Density (g / cm 3 )]]> Embodiment 1 500 610 50 1.6 Embodiment 2 540 620 52 1.6 Embodiment 3 520 610 51 1.6 Comparative Example 1 450 490 45 1.7 Comparative Example 2 390 410 40 1.9 Comparative Example 3 400 450 43 1.8

[0094] In summary, compared with the comparative example, the composite material prepared in this embodiment has higher tensile strength, flexural strength and impact strength, and lower density, indicating that its lightweight and high-strength properties are significantly improved. This is mainly due to the optimized ratio of multiple fibers and fillers used in the present invention, as well as the specific surface treatment and curing process.

[0095] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Lightweight and high-strength composite material, characterized by: The invention comprises the following raw materials in parts by weight: 30-50 parts of carbon fiber, 20-40 parts of glass fiber, 5-10 parts of nano silicon dioxide, 20-30 parts of polyamide, 40-60 parts of epoxy resin, 5-10 parts of curing agent, 2-5 parts of coupling agent, 3-8 parts of toughening agent and 1-3 parts of dispersant.

2. The lightweight and high-strength composite material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 40 parts of carbon fiber, 30 parts of glass fiber, 8 parts of nano silicon dioxide, 25 parts of polyamide, 50 parts of epoxy resin, 8 parts of curing agent, 4 parts of coupling agent, 6 parts of toughening agent and 2 parts of dispersant.

3. The lightweight and high-strength composite material according to claim 1 or 2, characterized in that: The carbon fiber is a high-strength carbon fiber with a tensile strength of not less than 5000 MPa and an elastic modulus of not less than 300 GPa.

4. The lightweight and high-strength composite material according to claim 1 or 2, characterized in that: The glass fiber is an alkali-free glass fiber, and its tensile strength is not less than 2000 MPa and its elastic modulus is not less than 70 GPa.

5. The lightweight and high-strength composite material according to claim 1 or 2, characterized in that: The curing agent is any one of an amine curing agent, an acid anhydride curing agent, and an imidazole curing agent; specifically, the amine curing agent is ethylenediamine, the acid anhydride curing agent is phthalic anhydride, and the imidazole curing agent is 2-methylimidazole.

6. The lightweight and high-strength composite material according to claim 1 or 2, characterized in that: The coupling agent is any one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent; specifically, the silane coupling agent is KH-550, the titanate coupling agent is NDZ-101, and the aluminate coupling agent is DL-411.

7. The lightweight and high-strength composite material according to claim 1 or 2, characterized in that: The toughening agent is any one of a thermoplastic elastomer, rubber particles, and a thermosetting resin; specifically, the thermoplastic elastomer is a polyurethane elastomer, the rubber particles are nitrile rubber particles, and the thermosetting resin is an epoxy resin toughening agent.

8. The lightweight and high-strength composite material according to claim 1 or 2, characterized in that: The dispersant is any one of a surfactant, a polymer dispersant, and an inorganic dispersant; specifically, the surfactant is sodium dodecyl sulfate, the polymer dispersant is polyvinyl alcohol, and the inorganic dispersant is silica microspheres.

9. The lightweight and high-strength composite material according to claim 1 or 2, characterized in that: The preparation method of the composite material comprises the following steps: Step 1: Preprocessing: Surface treatment of carbon fiber and glass fiber to remove impurities and oil stains on the fiber surface; Step 2: Prepare mixed resin: Adding nano-silicon dioxide into polyamide and epoxy resin, stirring evenly to obtain a mixed resin; Step 3: Preparing prepreg: Adding the surface-treated carbon fiber and glass fiber into the mixed resin and stirring evenly to obtain a prepreg; Step 4: Preparation of composite materials: Adding a curing agent, a coupling agent, a toughening agent and a dispersant into the prepreg, stirring evenly, to obtain a composite material raw material; Step 5: Hot Pressing: The composite material raw material is placed in a mold and hot-pressed to obtain a lightweight and high-strength composite material.

10. The lightweight and high-strength composite material according to claim 9, characterized in that: In step five, the hot pressing molding is performed at a pressure of 10-20 MPa, a temperature of 120-150° C., and a time of 1-2 hours.

Citation Information

Cited By

  • High-strength anti-corrosion electric circulating water pipeline reinforcing composite material and preparation method thereof

    CN120535909A

  • Anti-aging epoxy resin composite material and preparation method thereof

    CN121182148A